2016
DOI: 10.1007/s11356-015-6025-y
|View full text |Cite
|
Sign up to set email alerts
|

Influences of artificial root exudate components on the behaviors of BDE-28 and BDE-47 in soils: desorption, availability, and biodegradation

Abstract: Behaviors of BDE-28 and BDE-47 in two distinct soils (Phaeozem and Acrisol) as affected by the separate addition of root exudate components (i.e., oxalic acid, glycine, and fructose) were investigated by a soil microcosm incubation experiment. The results showed that root exudate components promoted the desorption of BDE-28 (57.6-235.0 %) and BDE-47 (56.9-223.7 %) from the soils due to the enhancement of their water solubilities. The addition of root exudate components increased the n-butanol extractability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Distinct changes in bacterial communities in CWs amended with artificial exudates were revealed by Illumina high-throughput sequencing. These results indicate the potential importance of LMWC compounds in influencing the structure of bacterial communities, in general agreement with other studies [22,29]. Some genera in our study responded positively to the artificial exudates; this result confirms previous studies suggesting that the most common sugars, organic acids, and amino acids associated with root exudate to rhizosphere are nutrient sources, chemoattractant signals, and promoters for microbial growth [30].…”
Section: Discussionsupporting
confidence: 93%
“…Distinct changes in bacterial communities in CWs amended with artificial exudates were revealed by Illumina high-throughput sequencing. These results indicate the potential importance of LMWC compounds in influencing the structure of bacterial communities, in general agreement with other studies [22,29]. Some genera in our study responded positively to the artificial exudates; this result confirms previous studies suggesting that the most common sugars, organic acids, and amino acids associated with root exudate to rhizosphere are nutrient sources, chemoattractant signals, and promoters for microbial growth [30].…”
Section: Discussionsupporting
confidence: 93%
“…Biodegradation was generally more pronounced in leachates from planted than from unplanted mesocosms. Plants can enhance pesticide sorption on SOM or/and minerals within the rhizosphere, while root exudates favour pesticide desorption and availability, thereby increasing biodegradation (Huang et al, 2016;Lefevre et al, 2013;Violante and Caporale, 2015). While microbial (co-)metabolism is a major degradation processes for anilide pesticides (Elsayed et al, 2014;Imfeld et al, 2018), the presence of a plant-root system in the soil can sustain rhizosphere microbial communities through root exudates, mainly consisting of labile organic matter (Mommer et al, 2016).…”
Section: Csiamentioning
confidence: 99%
“…The soil-plant system includes the rhizosphere, which is characterized by diverse and intense microbial activity, respiration processes and nutrient uptake, mainly controlled by the water circulation (Bardgett and Van Der Putten, 2014;Hinsinger, et al, 2009;Hinsinger, et al, 2006;Mommer et al, 2016;Zhang et al, 2017). While organic contaminants are hardly adsorbed to organic matter and soil minerals, the root exudates from plants favour their desorption and availability, being directly accessed by macro-and microorganisms and plants (Huang et al, 2016). Plant rhizosphere can enhance pesticide dissipation by sustaining specific microbial communities capable of 4 pesticide transformation (Diez et al, 2017), resulting in shorter pesticide half-lives in the rhizosphere compared to the bulk soil (Hand et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…LeFevre et al have observed that REs could enhance desorption of residual pollutants, thus improving bioavailability and subsequent biodegradation potential. Furthermore, Huang et al have shown the effects of REs components on desorption, availability, and biodegradation of BDE‐28 and BDE‐47 in soils. However, the effect of REs on the removal of TCS is seldom investigated.…”
Section: Introductionmentioning
confidence: 99%